Mainstreaming Water Energy Food Nexus thinking and drought preparedness into local municipal planning: An analysis in the Bergrivier Municipality - Thwala, Setsabile (Department of Environmental and Geographical Science, 2023)
The study explores the impacts of drought at a local scale focusing on the drought impacts on a local municipality and major employers through a Water Energy Food Nexus lens. The study is grounded on literature based on water-energy-food nexus, the sustainable livelihoods framework and drought. Given that natural disasters such as drought tend to affect water, energy and food, it is important to understand how municipal policy is set to try to manage these drought impacts and the interconnections that exist between these resources water, energy and food, as well as how these three resources affect local livelihoods. This study assumes that when trying to understand drought impacts on local access and use of water, energy and food as well as the influence on livelihoods, it is essential to also incorporate the municipality that not only acts as a service provider for household water and energy but also plays a role in disaster risk management in times of drought. Therefore, the interventions municipality may take during the drought may also have an influence on employers within the municipality and household use and access to water, energy and food. Employers play a role towards people's livelihood security as they contribute to households earning a living (income generating activities) and interventions taken by employers during the drought may have an influence on household livelihoods. Employers are also competing resource users of water and energy within a municipality, which is why it's important to include in them when looking at impacts of drought on water, energy food at the local scale. The study conducted interviews with Bergrivier Municipal Officials and employers to gain an understanding of their experiences and actions taken during the 2015-2018 drought. The study also made use of a desktop review to assess municipal policy with regards to drought preparedness and the extent to WEF Nexus thinking within the municipality. In conclusion the study found that the municipal still required extensive work towards acknowledging WEF Nexus thinking or the interdependencies that exist amongst these three resources holistically. Even so the WEF Nexus is still a growing concept that requires more time to be adapted by municipalities nationally and globally into their development planning.